The Illusion of Inclusion: Disempowered "Diversity" in 2018 Australian Children's Picture Books. Issue 2 (3rd July 2021) - Booth, Emily; Lim, Rebecca
ABSTRACT: Research into diverse representation in children's literature has predominantly focused on highlighting positive representations of marginalized communities, or critiquing overtly negative stereotypes. While important, this has resulted in the more innocuous representations of marginalized characters being overlooked in scholarship. This study discusses 35 2018 Australian children's picture books in which marginalized characters were depicted; yet their identities were not engaged with as part of an enjoyable narrative. These findings provide new insights for scholars, librarians, educators, readers, and publishers, that can support the identification of truly inclusive children's picture books.